The Coldest Coast
LXXIII, 250 p. 69 illus., 33 illus. in color.
Keywords: This book describes the 1873 voyage of the British explorer Benjamin Leigh Smith, based on the diaries and photographs of Lieutenant Herbert C. Chermside, who joined the expedition of the seas around Svalbard. Chermside’s photographs, long believed lost, have recently been uncovered in Sweden and are being curated there by the Grenna Museum. The three unpublished diaries of Herbert Chermside were lent to the Scott Polar Research Institute in 1939 by Mrs. Benjamin Leigh Smith. For the first time, Chermside’s diaries are published in their entirety, with the original photographs shown alongside modern images of the same locations. This includes the first photographic record of the north coast of Svalbard, images that are today being used as comparative data for the study of climate change in the archipelago. The diaries have been fully transcribed and edited. Introductory chapters are included, written by specialists in the history of exploration, history of science, and the history of photography from Penn State University, the University of Gothenburg, and UiT, the Arctic University of Norway, as well as contributors from the UK and Germany. This volume is published in association with Grenna Museum, which will present Chermside’s photographs in a 2022 exhibit on Leigh Smith and A.E. Nordenskiold.